Mechanical and Chemical Properties of Harvested Hypalon Cable Jacket Subjected to Accelerated Thermal Aging. (3rd June 2018) - Duckworth, Robert C.; Kidder, Michelle K.; Aytug, Tolga; Fifield, Leonard S.; Glass, William; Davis, Sarah
Abstract: For nuclear power plants (NPPs) considering second license renewal for operation beyond 60 years, knowledge of long-term operation, condition monitoring, and viability for the reactor components including reactor pressure vessel, concrete structures, and cable systems is essential. Such knowledge will provide NPP owners/operators with a basis for predicting performance and estimating the costs associated with monitoring or replacement programs for the affected systems. For cable systems that encompass a wide variety of materials, manufacturers, and in-plant locations, accelerated aging of harvested cable jacket and insulation can provide insight into a remaining useful life and methods for monitoring. Accelerated thermal aging in air at temperatures between 80°C and 120°C was conducted on a multiconductor control rod drive mechanism cable manufactured by Boston Insulated Wire (BIW). The cable, which had been in service for over 30 years, was jacketed with Hypalon and insulated with ethylene propylene rubber. From elongation at break (EAB) measurements and supporting Arrhenius analysis of the jacket material, an activation energy of 97.84 kJ/mol was estimated, and the time to degradation, as represented by 50% EAB at the expected maximum operating temperature of 45°C, was estimated to be 80 years. These values were slightly below previous measurements on similar BIW Hypalon cable jacket and could be attributed to either in-service degradation or variations in material properties from production variations. In addition, results from indenter modulus measurements and Fourier transform infrared spectroscopy suggest possible markers that could be beneficial in monitoring cable conditions.